Comparative analysis of MCDM methods for the assessment of sustainable housing affordability - Mulliner, Emma; Malys, Naglis; Maliene, Vida (Elsevier, 2016)
While affordability is traditionally assessed in economic terms, this paper tests a new assessment method that draws closer links with sustainability by considering economic, social and environmental criteria that impact on a household’s quality of life. The paper presents an empirical application and comparison of six different multiple criteria decision making (MCDM) approaches for the purpose of assessing sustainable housing affordability.